Peningkatan Literasi Ekonomi Syariah Pada Generasi Milenial - Bundo, Mayang; Wahyudi, M.; Nenengsih, Nenengsih; Putra, Doni Eka; Fitri, Radia (Tamkin Jurnal Pemberdayaan Tazkia, 2024)
Community service in the form of sharia economic literacy aims to provide students with understanding and insight regarding sharia economics both theoretically and practically, help students map out careers with the sharia economics study program and introduce STEI Ar Risale West Sumatra to SMA/MA students. Thus, the aim and target of implementing this PkM activity is that it is hoped that students will become driving agents and can contribute to the advancement of Sharia Economics in the city of Padang, West Sumatra.